1970
DOI: 10.3329/jom.v10i3.2008
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of Awareness in a Diabetic Population

Abstract: This cross-sectional survey was carried out during the period, October 2005 to December 2005, among 184 randomly chosen diabetic patients in Khulna Diabetic Centre, Khulna, Bangladesh, to evaluate the knowledge of the patients for their control of diabetes mellitus and also to explore the association(s) of their attitude and knowledge regarding diabetic awareness towards educational status and socio-demographic profile. In this study, we found a significant difference, in diabetic awareness to keep correct blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…14 Another study showed that education had a significant role in diabetic awareness to keep correct blood glucose level. 15 These findings are consistent with other studies. 12,13 Virtually, there are no epidemiological studies in Bangladesh assessing the level of diabetic education and knowledge both in diabetic and non-diabetic population.…”
Section: Discussionsupporting
confidence: 83%
“…14 Another study showed that education had a significant role in diabetic awareness to keep correct blood glucose level. 15 These findings are consistent with other studies. 12,13 Virtually, there are no epidemiological studies in Bangladesh assessing the level of diabetic education and knowledge both in diabetic and non-diabetic population.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, more than half (54.7%) of the participants reported that the cataract was a most common chronic complication of DM and kidney disease (45.6%), heart disease (40.4%) and amputation (20.8%). There areseveral studies that have shown similar results regarding the potential complications of DM (25,26). More than half of the patients identified cataract as a complication of DM.…”
Section: Knowledge Score On Complications Of Diabetessupporting
confidence: 48%
“…More than half of the patients identified cataract as a complication of DM. However, the knowledge regarding diabetic eye disease was poor.A study done by Hogue et al (2006) in Bangladesh found that only 4.9% oftheir study participants were aware oftheir study participants were aware of diabetic eye disease (26). In contrast to the studies done in South Asia, the majority (92%) of the participants in Moodley et al (2007) study in South Africa had identified blindness as the main complication of DM (13).…”
Section: Knowledge Score On Complications Of Diabetesmentioning
confidence: 48%
“…The utilization of diabetic service was influenced by demographic, socio-economic and educational factors which were supported by numerous studies in developed and developing countries [ 30 ]. On the other hand, educational qualification does not influence the patients to visit diabetic services reported by a hospital based study in Bangladesh [ 31 ]. Many studies from developed and developing countries reported that women generally enjoy less health care facility [ 32 ].…”
Section: Discussionmentioning
confidence: 99%